2022
DOI: 10.1007/s11151-022-09886-7
|View full text |Cite
|
Sign up to set email alerts
|

Patent Licensing and Capacity in a Cournot Model

Abstract: We consider the problem of patent licensing in a Cournot duopoly in which the innovator (patentee) is one of the firms and it is capacity constrained. We show that when the patentee can produce a relatively small (relatively large) quantity, it prefers licensing by means of a fixed fee (unit royalty). When the patentee can set two-part tariffs in the form of combinations of fixed fees and unit royalties, it charges a positive fixed fee if and only if it is limited to producing a relatively small quantity. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hong et al (2022) found that, in addition to innovativeness of patentees, absorptive capacity of licensees may significantly affect licensing strategy and patentees may prefer unit royalty licenses and two-part ad valorem licenses to fixed-fee licensing contracts. Colombo et al (2023) argued that, when innovator's capacity is constrained (i.e., patentee can produce relatively small quantities), it prefers to license by using a fixed-fee strategy, and conversely, patentee prefers unit royalty licensing strategy. It showed that green manufacturers should choose a fixed-fee licensing strategy when market size expansion effect is strong and competition intensity is moderate; otherwise, green manufacturers should choose a royalty licensing strategy.…”
Section: Technology Licensingmentioning
confidence: 99%
“…Hong et al (2022) found that, in addition to innovativeness of patentees, absorptive capacity of licensees may significantly affect licensing strategy and patentees may prefer unit royalty licenses and two-part ad valorem licenses to fixed-fee licensing contracts. Colombo et al (2023) argued that, when innovator's capacity is constrained (i.e., patentee can produce relatively small quantities), it prefers to license by using a fixed-fee strategy, and conversely, patentee prefers unit royalty licensing strategy. It showed that green manufacturers should choose a fixed-fee licensing strategy when market size expansion effect is strong and competition intensity is moderate; otherwise, green manufacturers should choose a royalty licensing strategy.…”
Section: Technology Licensingmentioning
confidence: 99%
“…A similar study has addressed the problem of patent licensing in a Cournot duopoly, where one of the firms acts as the innovator (patentee) and encounters capacity limitations. The focus of this study revolves around investigating the challenges associated with patent licensing within the context of a Cournot duopoly, where one firm holds the role of the patentee and faces capacity constraints [23]. Another study focused on a differentiated Cournot model and a differentiated Bertrand model, in which one of the firms engages in an R&D process resulting in an endogenous cost-reducing innovation [24].…”
Section: Introductionmentioning
confidence: 99%